Students’ Difficulties in Pronouncing Fricative Consonant - Imam Tarmizi Situmeang; Rayendriani Fahmei Lubis (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
The article aims to identify the students’ difficulties in pronouncing fricative consonants and the factors that impede their pronouncing those consonants. A descriptive qualitative method was employed where 9 students at the fourth semester of TBI-2 in Tarbiyah and Teacher Training Faculty IAIN Padangsidimpuan involved in this study. The data present that the students’ difficulties in pronouncing English fricative consonant sounds are; the different elements between native language and the target language (/q/,/ð/,/ò/), the same phonetic feature in both language but differ in their distributions (/v/,/f/,/ჳ/,/z/,/s/and/h/). The study found that the dominant difficulty in producing English Fricative sounds are sound /ð/- voiced dental fricative in initial word position and /q/- voiceless dental fricative in initial word position. 9 out of 9 students mispronounce sound /ð/ and 9 out of 9 students mispronounce sound /q/. All of the students pronounce sound /ð/ and /q/ inappropriately. Whereas, the factor of its difficulties are the effect of mother tongue or first language, unsuccessful in using borrowed English words, lack of knowledge about English fricative sounds, prefers to speak Batakness rather than English and less of pronunciation practice.